(untitled) (Bangladesh Journal of Animal Science, 2025)
A baseline survey on management practices with some background parameters of dairy farms was conducted at Gazipur sadar upazilla, Sreepur upazilla, Kapasia upazilla and Kaligonj upazilla of Gazipur district during January to June, 2022. Data was collected with structured questionnaire from a total of 115 dairy farms. The farm size varied from 10 to 150 dairy cattle, with majority of the farms contained between 15 to 40 dairy cattle. The highest 91.76% and 16.0% of the farmers were male and female in Kaligonj upazilla and Sreepur upazilla, respectively. The farmers had a wide range of educational background from primary to higher secondary or above. The highest 35.72% of the farmers were engaged in business in Gazipur sadar upazilla. The highest 59.53% of the farmers used own capital in Gazipur sadar upazilla. Most (59.52%) of the farmers did not have any training on cattle farming in Gazipur sadar upazilla. The highest 76.19%, 83.33%, 76.19%, 83.33%, 83.33% and 95.83% of the farmers took help from govt. office, regularly used vaccine against infectious diseases, took help from veterinary surgeon for the treatment, used vitamin and mineral supplements, used feed according to body weight and production and used antibiotics for the treatment in Gazipur sadar upazilla and Kapasia upazilla, respectively. The highest 76.0% of the farmers followed scientific/hygienic way of milking and milk handling, and 68.0% followed scientific/hygienic way of storage and transportation of milk in Sreepur upazilla. The results of this study provided a clear picture of the level of farm management practices among the dairy farms of Gazipur district which will be useful for farmers and researchers to identify the overall situations with problems and their remedies on management related to dairy farms in Bangladesh. Bangladesh Journal of Animal Science 54 (2): 36-43, 2025